(untitled) (The Pakistan Development Review, 2000)
It is frequently asked whether the modern economy can function without interest. This question has acquired some urgency in wake of the recent ruling of Supreme Court banning interest in Pakistan. In this respect every expert has his own opinion. Some pronounced that great harm will result from the banning of interest. Others have the opinion that such pronouncement is based on lack of understanding of the modern economic system, as well as the nature of the Islamic prohibition of interest. However, the banning of the rate of interest has affect on the economic activity, i. e. especially on the small traders and farmers. It is commonly argued that this change in capital market has two important effects on the economy. It increased the capital supply while price reduces, thus improving efficiency. And it makes also possible to produce more with relatively less cost, thus has positive effect on the growth of the economy